Osmotic demyelination syndrome with normal serum sodium in an alcohol-dependent patient: a case report - Li, Yaqi; Han, Lu; Jiang, Yumeng; Zhao, Zhihong; Xin, Zikai; Zhu, Zilong (Frontiers in Human Neuroscience, 2025)
Osmotic demyelination syndrome (ODS), which embraces central pontine myelinolysis and extrapontine myelinolysis, is a well-known but uncommon disorder of the central nervous system. The disease primarily occurs after rapid correction of severe hyponatremia. However, excessive drinking is one of the rare etiologies of ODS. Cases of alcohol-related ODS without documented hyponatremia are rarely reported, and optimal therapeutic approaches remain unclear. We report a patient in his 30’s with a history of heavy drinking who presented with unsteady gait and limb tremor as the main clinical manifestations. The patient consistently denied any history of fluid or electrolyte imbalances and reported a normal-range blood sodium level. Magnetic resonance imaging (MRI) revealed triangular T2-weighted and FLAIR pontine hyperintensity with a surrounding DWI rim. Finally, the patient recovered completely following corticosteroid treatment. This case shows the possibility that Alcohol-related ODS can occur without electrolyte disturbances and may respond favorably to combined corticosteroid and vitamin B therapy, warranting further investigation in clinical studies. We conducted a literature review of ODS in alcoholic patients and summarized its possible etiology, epidemiology, clinical characteristics and treatment options to raise awareness of such disorders.